Introduction to Kubernetes. (O'Reilly Media, Inc., 2021)
If your company is about to embrace containers and develop microservices-type applications, this course will get you started. You'll get a hands-on tour of Kubernetes core concepts covering installation, configuration, and the API resources to use for your containerized applications. You'll learn how you can use Kubernetes primitives to build a distributed application that can scale and make efficient use of containers. As the course comes to a close, you'll have a clear understanding of how to take your container images to production, build a complex distributed application, and manage it in your data-center. In short, you'll be well positioned to usher your company into the world of containers. What you'll learn and how you can apply it By the end of this course, you'll understand: The Kubernetes cluster architecture Basics of Kubernetes installation The API resources and endpoints How to interact with a Kubernetes cluster using kubectl How to use the Kubernetes primitives to build a scalable containerized application And you'll be able to: Interact with a Kubernetes cluster using the API and the kubectl CLI Build distributed applications using the core API resources Explore all the Kubernetes primitives and understand how they will integrate with their enterprise workflow and processes. Perform rolling-updates and rollbacks of your applications Expose your applications using Kubernetes services Monitor your cluster using Prometheus This course is for you because... You're an application developer and want to understand how to prepare your containerized application for Kubernetes. You're an application developer who is building Docker images and want to learn how to use those images in Kubernetes. You're an application developer and want to understand the Kubernetes core API objects to configure your application You're a system administrator and want to understand how to manage containerized applications in a cluster. You're a system administrator and want to run system daemons in your cluster like the same way you manage end-user application. You're a system administrator and want to understand how to monitor and collect logs in a Kubernetes cluster. Prerequisites Install minikube Install kubectl Create a deployment with kubectl run ghost --image=ghost Scale that deployment, check the Pods Check kubectl --help what can you do ? Recommended Preparation: CLI for Noobies: A Primer on the Linux Command Line.